2011
DOI: 10.5007/1980-0037.2010v12n2p164
|View full text |Cite
|
Sign up to set email alerts
|

Fenótipo da gordura, fatores associados e o polimorfismo rs9939609 do gene FTO DOI:10.5007/1980-0037.2010v12n2p164

Abstract: Resumo -O propósito deste foi sintetizar os principais resultados de estudos que analisaram a relação do polimorfismo de nucleotídeo simples (SNP) rs9939609 do gene FTO (fat mass and obesity associated), com a manifestação de sobrepeso / obesidade e suas co-morbidades e discutir a interação deste polimorfismo com os demais fatores promotores da obesidade. A busca foi realizada nas bases de dados MEDLINE, Highwire, Science Direct e SciELO, usando as palavras-chave: FTO rs9939609, obesity genetic, gene associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
5
0
4
Order By: Relevance
“…Obesity is a multifactorial condition with a strong lifestyle-allied influence. It is determined by environmental as well as genetic factors, triggering several other diseases [25] [28] [29]. Familial history has been identified as a chief risk factor for several chronic diseases of public health significance, including obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a multifactorial condition with a strong lifestyle-allied influence. It is determined by environmental as well as genetic factors, triggering several other diseases [25] [28] [29]. Familial history has been identified as a chief risk factor for several chronic diseases of public health significance, including obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, FTO is a highly polymorphic gene located on chromosome 16q12.2, and several of its variants have been associated with energy regulation and body mass index (BMI) [10][11][12][13][14]. Among the polymorphisms, rs9939609 has been the most thoroughly studied and annotated to be associated with the obesity phenotype [15,16]. Additionally, ghrelin, a peptide produced in the stomach, has important roles in growth hormone secretion, appetite stimulation, food intake, regulation of gastric motility and acid secretion, adiposity, energy homeostasis and inflammatory processes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that explain why the polymorphisms of the rs9939609 of the FTO gene influence in the accumulation of body adiposity have not yet been elucidated 27 . However, Benedict et al 28 found that FTO may facilitate weight gain by increasing grelin (hunger hormone) and decreasing leptine (saciety hormone) plasma levels.…”
Section: Discussionmentioning
confidence: 99%